Workplace spirituality: Reflections on generating meaning through Jewish perspectives of kedusha (Holiness) - Kay, Avi (Journal for the Study of Spirituality, 2022)
Interest in spirituality in the workplace continues to grow. Research has shown how experiencing spirituality in the workplace is associated with finding meaning from work, which has been, in turn, associated with both personal and organizational benefits. This article reflects on how an understanding of kedusha (holiness) in both traditional and contemporary Jewish sources can augment a sense of workplace spirituality. Specifically, it illustrates how the Jewish understanding of kedusha highlights both the need for individual agency and a sense of community for the achievement of spirituality in the workplace. Some implications of this for contemporary organizations are presented for consideration.